International relations theory and South Asia: security, political economy, domestic politics, identities, and images - Sridharan, Eswaran (Oxford University Press, 2011)
This volume, by a diverse group of South Asian scholars, goes beyond conflict management and looks forward to building a larger regional entity. Drawing on international relations theory and social science, it tries to find long-term answers to conflict resolution
Includes bibliographical references
Keywords: South Asia -- Economic policy; South Asia -- Foreign relations; South Asia -- Politics and government